Efektivitas Implementasi Kebijakan Pengambilan Keputusan Kebijakan Subsidi Pupuk Di Desa Tumpakpelem Kecamatan Sawoo Kabupaten Ponorogo - Wahyu Priandanata; Danni Andreas; Adam Jamal (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Ponorogo Regency is an area that is mostly dominated by mountains with the majority of the population making their living as farmers. So fertilizer is one of the important components used by farmers to support the farming period, which contains one or more nutrients or nutrients for plants to support plant growth and development. One of the policies in fertilizer procurement is fertilizer subsidies. Minister of Agriculture Regulation number 10 of 2022 concerning procedures for determining the allocation and highest retail price for subsidized fertilizers in the agricultural sector, which at the implementation stage still faces many problems. From the results of survey research with data collection using the direct interview method with the aim of describing the procedures for implementing the subsidized fertilizer program through the Tani Card and assessing the effectiveness of the subsidized fertilizer policy for farmers. It shows that this policy has so far been felt to be ineffective, giving rise to farmers' dissatisfaction with the subsidized fertilizer that has been provided, resulting in an impact on the quality and low yields of the harvest. Policy revisions and tighter supervision are needed to ensure that the fertilizer subsidy program can run effectively and on target to support national food security.